Software process improvement in a start-up with a focus on communication between teams - Badulina, Anna; Kučera, Jan; Malcová, Dana; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2022)
The purpose of this study is the practical implementation of improving the software development process in a startup company, based on a theoretical framework. Improvements will focus on communication between frontend and backend teams in a startup. The analysis and evaluation of the company and interviews among the project participants revealed the main problems of the start-up under study. After prioritizing and identifying the dependencies of problems from each other, a breakdown of dependency on management was chosen for further improvement. This problem was that the Backend and Frontend team is forced to communicate through intermediaries: the Project Manager and the Product Owner. To solve the identified problem, trainings were undertaken for developers and management staff for which the rules of communication were revised, aimed at eliminating the bottleneck.
Vedoucí práce: Jan Kučera
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: information systems management [obor dipl. práce]; diplomové práce; master's theses